Firing characteristics of swallowing interneurons in the dorsal medulla during physiologically induced swallowing in perfused brainstem preparation in rats. (April 2022) - Yamamoto, Ryota; Sugiyama, Yoichiro; Hashimoto, Keiko; Kinoshita, Shota; Takemura, Akiyo; Fuse, Shinya; Kaneko, Mami; Mukudai, Shigeyuki; Umezaki, Toshiro; Dutschmann, Mathias; Nakagawa, Takashi; Hirano, Shigeru
Graphical abstract: Highlights: Activities of swallowing neurons during physiologically evoked swallow were assessed. About half neurons were inactive without response to pharyngolaryngeal afferents. For individual neurons, the peak activities were varied based on swallowing onset. Neuronal modulations by capsaicin injection were modest compared to water injection. Abstract: Oropharyngeal swallowing is centrally mediated by a swallowing central pattern generator (Sw-CPG) in the medulla oblongata. The activity of the Sw-CPG depends on the sensory inputs determined by physical and chemical bolus properties. Here we investigate the sensory-motor integration during swallowing arising from different sensory sources. To do so we electrically stimulated the superior laryngeal nerve and we triggered swallowing with oral injections of distilled water or capsaicin solution and extracellularly recorded from swallowing interneurons in arterially perfused brainstem preparations of rats. We recorded the activities of 40 neurons, while monitoring the motor activities of the phrenic, vagal and hypoglossal nerves. Eighteen neurons responded to electrical stimulation of the ipsilateral superior laryngeal nerve, and 6 neurons were excited by oral fluid injection, while 16 non-respiratory neurons did not receive afferent inputs to either electrical or physiological stimuli. The cellular activities displayed by swallowing interneurons during electrical and physiological stimulation of pharyngeal and laryngeal afferent input reveal complex adaptations of the timing of firing patterns and frequencies. The modulation of neuronal activity is likely to contribute to the coordination of efficient bolus transfer during the pharyngeal stage of swallowing.